An Intelligent Surgery Information System Using RFID for Internet of Things - Hung, Lun-Ping; Tang, Shen-Yuan; Chen, Chien-Liang; Yang, Shih-Yang (EAI Endorsed Transactions on Internet of Things, 2019)
The Internet of Things (IoT) enables new hospital information system by using RFID technology. It becomes the key mechanism for IoT. RFID technology is not only help us to identify doctors, nurses or patients in the hospital information system, but also track doctors, nurses or patients in the hospital. More and more data is being collected into the system in order to achieve an intelligent information system. In this study, we develop an intelligent surgery information system to reduce writing errors caused by human negligence and reduce nurse’s and physician’s workload and elevate the quality of patient care. The study was conducted at a medical center located in northern Taiwan. Through the establishment of the proposed intelligent surgery information system, documents used in surgeries are eliminated and are recorded in computers. The intelligent surgery information system combines HIS, PACS and LIS to assist medical personnel to import patient’s clinical records, imaging reports, inspection reports and other relevant information before, during and after surgery. We propose the record, re-check, report and reference, the 4R checking mechanism as the core concept of the development of the proposed intelligent surgery information system. The checking mechanism can automatically view the completion of medical record, and maintain a high degree of integrity if the records are incomplete. After launching the system one and half year, we conduct a questionnaire survey and collect data from nurses and physicians who use this system. The survey was designed to measure the successfulness of the intelligent surgery information system. Questions focused on three broad areas: information quality, system quality, and users’ satisfaction. The results confirmed a high degree of satisfaction among users. According to the feedback, it shows that the system should improve the function of automatic saving on regular basis.